2014
DOI: 10.1371/journal.pntd.0002950
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Dengue Virus Transmission and Factors Associated with the Presence of Anti-Dengue Virus Antibodies in Humans in Three Major Towns in Cameroon

Abstract: BackgroundDengue is not well documented in Africa. In Cameroon, data are scarce, but dengue infection has been confirmed in humans. We conducted a study to document risk factors associated with anti-dengue virus Immunoglobulin G seropositivity in humans in three major towns in Cameroon.Methodology/Principal FindingsA cross sectional survey was conducted in Douala, Garoua and Yaounde, using a random cluster sampling design. Participants underwent a standardized interview and were blood sampled. Environmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 43 publications
7
68
0
4
Order By: Relevance
“…Our results confirm, however, that DENVs circulates in Cameroon as previously described [9], and that dengue 1 is re-emerging in Kribi as the first confirmed case was described in this city in 2000 [18]. The frequency of 3.3% anti-dengue IgM observed is significantly higher than that obtained in other cities in Cameroon during serosurveys; 0.3% IgM in Douala and 0.1% in Garoua by Demanou et al [8] in 2006/2007. This result shows that the Londji health area could have characteristics favorable of the spread of DENV 1, as well as the presence of Aedes mosquito, immunocompromised human groups, continuous introduction and/or circulation of one or more serotypes, some environmental parameters (temperature and precipitation affect the demography and behavior of Aedes vectors), international travel, poverty, and lack of sustained programs at various levels.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results confirm, however, that DENVs circulates in Cameroon as previously described [9], and that dengue 1 is re-emerging in Kribi as the first confirmed case was described in this city in 2000 [18]. The frequency of 3.3% anti-dengue IgM observed is significantly higher than that obtained in other cities in Cameroon during serosurveys; 0.3% IgM in Douala and 0.1% in Garoua by Demanou et al [8] in 2006/2007. This result shows that the Londji health area could have characteristics favorable of the spread of DENV 1, as well as the presence of Aedes mosquito, immunocompromised human groups, continuous introduction and/or circulation of one or more serotypes, some environmental parameters (temperature and precipitation affect the demography and behavior of Aedes vectors), international travel, poverty, and lack of sustained programs at various levels.…”
Section: Discussionsupporting
confidence: 91%
“…We found 14.3% acute dengue infection with 10.9% detected by real-time RT-PCR and 3.3% by MAC ELISA. These findings extend those of Demanou et al [8] who reported a seroprevalence of 0.3% in Douala and 0.1% in Garoua for dengue in 2011, confirming that DENV is circulating in Cameroon. The frequency of dengue detection obtained in this work is similar to the one obtained by Beckett et al [15] working on the early detection of dengue using 785 cluster volunteers around index cases, who found that 11 and 2 DENV cases by RT-PCR, respectively, in febrile and asymptomatic participants showing the first documentation of asymptomatic viremia in naturally acquired human dengue infections.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations